Manganese-pyrochloric acid photosensitizer nanocomplexes against osteosarcoma: achieving both high activatability and high effectiveness - Zhang, Xuran; Wang, Jian; Feng, Qun; Lei, Li; Zhu, Zhiyong (Frontiers in Bioengineering and Biotechnology, 2025)
Introduction The application of photodynamic therapy (PDT) is limited by unsatisfactory therapeutic efficacy and dose-dependent phototoxicity in clinical settings. Intravenous nano-drug delivery systems (NDDSs) hold promise for enhancing the delivery efficiency of photosensitive drugs, but often result in aggregation-caused quenching (ACQ) effects, preventing site-specific activation. Methods We exploited manganese (Mn2+)–pyrochloric acid (PPa) nanocomplexes coordinated using the photosensitizer PPa and metal Mn ion for the treatment of osteosarcoma. The nanocomplexes were precisely co-assembled in water to stably co-deliver Mn2+ and PPa, enabling tumor-specific release and fluorescence recovery. Results Following laser irradiation, the activated PPa significantly enhanced the killing effects on primary cancer cells. Additionally, Mn2+ ions activated the cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) pathway, promoting maturation of dendritic cells (DCs) and augmenting CD8+-mediated antitumor immune responses. Discussion This study advances the on-demand activation of photosensitive drugs and photodynamic immunotherapy toward clinical applicability by exploiting Mn2+–PPa nanocomplexes with high activatability and effectiveness for targeted PDT and immunotherapy.